Design and analysis of wideband circularly polarized dielectric resonator antenna for wireless communication applications - Khalajmehrabadi, Ali (2012)
Recent advancements in antenna structures have gathered lots of attention toward dielectric resonator antennas (DRAs). Wide impedance bandwidth, low dispersion loss, and high efficiency are the highlighted characteristics that caused DRAs to be the focus point of scholars and industry. Besides, there is a need to have a circular polarized antenna to alleviate the problem of having the same transmitter and receiver orientation. For circular polarization, several designs have been proposed. In order to have a higher axial ratio bandwidth, most of the proposed structures suggest having a two feed mechanism. Although they have a higher CP bandwidth rather than single feeding structures, the complexity in fabrication is a problem. Thus, there is a great need to have structures with a single feeding method and high axial ratio bandwidth. This thesis represents a novel DRA configuration that is excited with a simple micro strip feed line with a truncated ground plane. Thus, the fabrication is simplified via one feeding mechanism. Besides, a square shape notch is created inside the DRA patch and is rotated 45 degrees to create a low axial ratio. Since the whole structure is mounted vertically on the edge of its substrate, the high radiation resulted in a wide matching band width. The proposed compact DRA antenna showed a good radiation characteristic with an impedance bandwidth of 5.9GHz between 3.9GHz and 9.8GHz and axial ratio of 1.25GHz between 3.9GHz and 5.15GHz and axial ratio of 900MHz between 7GHz and 7.9GHz.